2010
DOI: 10.1177/0145482x1010400405
|View full text |Cite
|
Sign up to set email alerts
|

Visual Search Training and Obstacle Avoidance in Adults with Visual Impairments

Abstract: This study assessed the effect of visual search training on the avoidance of obstacles by adults with visual impairments. A significant reduction in contacts with obstacles under mesopic conditions was found in individuals who received search training. This finding suggests that search training had a positive effect on mobility performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 13 publications
1
17
1
Order By: Relevance
“…Moreover, there was also no improvement in regard to safety in either of the training groups, which indicates that the subjects did not become familiar with the course by repetition, as we would then expect fewer collisions. This finding is in contrast with the findings by Kuyk et al [ 19 ], where walking speed did not improve after EST training in AMD patients, who were assumed to have normal peripheral vision. However, the subjects in the current study significantly reduced the number of collisions with obstacles only in the dim walking conditions.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, there was also no improvement in regard to safety in either of the training groups, which indicates that the subjects did not become familiar with the course by repetition, as we would then expect fewer collisions. This finding is in contrast with the findings by Kuyk et al [ 19 ], where walking speed did not improve after EST training in AMD patients, who were assumed to have normal peripheral vision. However, the subjects in the current study significantly reduced the number of collisions with obstacles only in the dim walking conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…This demonstrates that top-down information processing is involved in successful vision rehabilitation. Similar results were obtained by Kuyk and colleagues who studied the effect of exploratory saccade training (EST) in a large cohort of patients with vision loss [ 19 ]. They found that patients' performance in exploratory tasks improved with training and led to fewer collisions with obstacles under dim conditions.…”
Section: Introductionsupporting
confidence: 84%
“…Several recent studies have reported benefits of visual search training for mobility in patients with low vision, mostly under conditions of low luminance or contrast 14, 15 . The present results suggest that the main oculomotor change with the use of peripheral vision is an increase in fixation instability.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work suggests that training on a visual search task can improve mobility performance under low light conditions for people with visual impairments including AMD 14, 15 . To develop novel rehabilitation interventions, a better understanding of the short-term oculomotor adaptations of the visual system following scotoma onset is needed.…”
mentioning
confidence: 99%
“…Visual search in people with visual impairment has been suggested as a predictor for mobility and performance of other daily activities (Kuyk et al 2005). There is evidence for the effectiveness of eye movement training on visual search in congenital prosopagnosia (Schmalzl et al 2008), following brain damage (Bouwmeester et al 2007), and for improved visual search and mobility performance in people with visual impairment of ocular origins following repeated practice of an item-based search task (Kuyk et al 2010;Liu et al 2007). These types of findings could lead to interventions and alternative approaches to management of patients.…”
Section: Open Peer Commentarymentioning
confidence: 99%